Site Specific Response Analysis (SSRA) Kampus UNP Air Tawar, Kota Padang - Misriani, Merley; Alexander, Hendra; Hamid, Desmon; Aguskamar, Aguskamar; Wisafri, Wisafri (Jurnal Ilmiah Rekayasa Sipil, 2017)
In general, the seismic design provisions around the world present different criteria for local soil conditions depending on soil and rock properties to determine the design spectra representing seismic design. On the other hand, site-specific analysis results not only show the main characteristics of soil-rock profiles but also local soil characteristics where detailed studies are needed to review the earth response to earthquakes. In this study conducted Site Specific Response Analysis (SSRA) is to analyze the earthquake wave propagation from the bedrock to the surface layer. The data needed are ground stratification data and shear wave velocity parameters obtained from empirical correlation to N-SPT test drilling data. In addition, the required data is ground motion synthetic at baserocks used for the earthquake wave propagation obtained by Probabilistic Seismic Hazard Analysis (PSHA) 3-dimensional earthquake source referring from the results of previous research. SSRA is based on the theory of single-dimensional wave propagation in time domain using NERA (Non-linear Earthquake Response Analysis) program. Various inputs of earthquake movement are taken by considering suitable for Padang area. The results of this analysis are shown in the form of historical time acceleration graph and peak acceleration from each bore point location which is then processed to obtain amplification and response spectra design factors for the re-quake period of 475 years and 2475 years.